Helium-Neon systematics in OIB and the nature of the source of mantle plumes - Moreira, Manuel (2011)
He and Ne isotopic analysis were performed on olivine phenocryts from several Islands (Santa Helena, Gough, Tristan da Cunha, Azores, Kerguelen and Hawaii) leading to the conclusion that Ne is a more sensitive tracer of primordial mantle material than helium.